Ethnic Identity and the Risk of Schizophrenia in Ethnic Minorities: A Case-Control Study - Veling, Wim (Oxford University Press, 2010)
Objectives: The high incidence of schizophrenia in immigrant ethnic groups in Western Europe may be explained by social stress associated with ethnic minority status. Positive identification with one's own ethnic group is a strong predictor of mental health in immigrants. We investigated whether negative ethnic identity is related to schizophrenia risk in non-Western immigrants. Methods: Matched case-control study of first-episode schizophrenia, including 100 non-Western immigrant cases, general hospital controls (n = 100), and siblings (n = 63). Conditional logistic regression analyses were used to investigate associations between schizophrenia and ethnic group identity. Results: Cases had a negative ethnic identity more often than general hospital controls (64% and 35%, respectively, P < .001). After adjustment for marital status, level of education, unemployment, self-esteem, social support, and cannabis use, negative ethnic identity was associated with schizophrenia: odds ratio = 3.29; 95% confidence interval = 1.36–7.92. Cases significantly more often had an assimilated or a marginalized identity and less often had a separated identity. Comparisons between cases and siblings largely confirmed these findings. Conclusions: Negative identification with the own ethnic group may be a risk factor for schizophrenia in immigrants living in a context of social adversity.